Development of Unconventional Nano‐Metamaterials from Viral Nano‐Building Blocks. Issue 13 (29th April 2022) - Passaretti, Paolo; Schofield, Zoe; Rickard, Jonathan James Stanley; White, Henry; Mahajan, Sumeet; Goldberg Oppenheimer, Pola
Abstract: Structured metamaterials are periodically arranged nanostructures in which the dielectric constant is periodically modulated on a length‐scale comparable to the desired wavelength of operation. Interactions of the electric fields of light waves with the sub‐wavelength unit structures can produce effects that are impossible in natural materials. Here, a technique to construct three‐dimensional (3D) metamaterials using self‐assembling M13 viral building‐blocks as templates which are then replicated into a metal quasi‐3D nanostructure is developed. By correct fit of virus fragments, it is possible to employ them in a LEGO‐like way to build up well‐defined structures on the nanoscale. The virus blocks are designed to spontaneously assemble into 3D‐periodic network structures with interesting optical properties. Subsequently, templating of these nanostructures into inorganic materials allows the replication of their network into an inverse periodic metal structure, which has the appropriate architecture for optical metamaterials. Establishing such a technique provides an important link toward the realization of applied metamaterials potentially heralding a new era for developing novel types of bio‐synthetic optical materials. These materials have a wide range of potential uses including cloaking materials, light‐storage devices, high‐speed optical computers and nano‐lasers, and will offer numerous applications in transformation optics. Abstract : A new technique to construct nano‐metamaterials using self‐assembling viral building‐block templates is replicated into a metal quasi‐3D nanostructure. By correct fit of virus fragments, they are employed to build up well‐defined periodic network structures on the nanoscale with interesting optical properties. Replication of their network into an inverse periodic metal structure yields the appropriate architecture for optical metamaterials.